2008 11th IEEE High Assurance Systems Engineering Symposium 2008
DOI: 10.1109/hase.2008.37
|View full text |Cite
|
Sign up to set email alerts
|

Randomization Based Probabilistic Approach to Detect Trojan Circuits

Abstract: In this paper, we propose a randomization based technique to verify whether a manufactured chip conforms to its design or is infected by any trojan circuit. A trojan circuit can be inserted into the design or fabrication mask by a malicious manufacturer such that it monitors for a specific rare trigger condition, and then it produces a payload error in the circuit which alters the functionality of the circuit often causing a catastrophic crash of the system where the chip was being used. Since trojans are acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…For example, Jha and Jha presented a randomization-based probabilistic approach to detect Trojans. 18 They showed that it's possible to construct a unique probabilistic signature of a circuit on the basis of a specific probability for patterns applied to its inputs. They apply input patterns based on the specific probability to IUA and compare its outputs with the original circuit.…”
Section: Trojan Activation Methodsmentioning
confidence: 99%
“…For example, Jha and Jha presented a randomization-based probabilistic approach to detect Trojans. 18 They showed that it's possible to construct a unique probabilistic signature of a circuit on the basis of a specific probability for patterns applied to its inputs. They apply input patterns based on the specific probability to IUA and compare its outputs with the original circuit.…”
Section: Trojan Activation Methodsmentioning
confidence: 99%
“…The testing phase detection methods attempt to enhance traditional IC testing, or use side-channel analysis. For logic testing, Jha and Jha present a randomisation-based technique which probabilistically compares the functionality of the design of the circuit with the implemented circuit [19]. Chakraborty et al suggest to test rare occurrences on an IC rather than testing for correctness [12].…”
Section: Introductionmentioning
confidence: 99%
“…A randomization based probabilistic approach to detect Trojan is presented in [14]. The authors show that it is possible to construct a unique probabilistic signature of a circuit using specific probability on its inputs.…”
Section: Introductionmentioning
confidence: 99%